Childhood Asthma Surveillance using Administrative Data: Consistency between Medical Billing and Hospital Discharge Diagnoses - France Labrèche; Tom Kosatsky; Raymond Przybysz (Canadian Respiratory Journal)
BACKGROUND: The absence of ongoing surveillance for childhood asthma in Montreal, Quebec, prompted the present investigation to assess the validity and practicality of administrative databases as a foundation for surveillance.